On mechanisms of antitumor action of tropolon series compounds - G. V. Zhukova; E. A. Lukbanova; T. P. Protasova; E. V. Zaikina; A. A. Kiblitskaya (Исследования и практика в медицине)
The review provides information on the mechanisms of the antitumor action of natural and synthetic compounds of the tropolone series, obtained over the past 30 years in studies on cell cultures and, to a lesser extent, in in vivo experiments. Interest in this group of substances is due to the urgent need of clinical oncology for drugs that effectively damage malignant cells and, at the same time, are safe for healthy tissues. The processes that realize the effects of colchicine, hinokithiol (ß-tuyaplicin) and some of their derivatives (derivatives of bistropolone, α-substituted tropolones, etc.) have been studied most fully. Herewith, more numerous mechanisms of realization of the antitumor effect of hinokithiol and its derivatives were revealed in comparison with colchicine. In addition to the disruption in the formation of the cell division spindle, shown for colchicine and colchamine, such phenomena as caspase-dependent apoptosis and some other types of apoptosis, autophagy, limitation of mitochondrial metabolism, DNA damage and demethylation, and accelerated aging of malignant cells etc. have been described. The promising properties of 2‑quinolyl 1,3‑tropolone derivatives have been shown, and the relationship of their antitumor effect with the induction of apoptosis and changes in the activity of the ERK signaling pathway in some types of malignant cells have been revealed. The results indicate a multiplicity of possible ways of the influence of tropolones on the state of malignant cells, the conditions for the implementation of ones need to be clarified, especially with a lack of information about in vivo processes.The review includes information from the literature presented in the Scopus, WoS, Pubmed databases. 35 % of articles have been published in the last 5 years.